Advanced Ultrasound Technology and Its Application to Gynecologic Practice [11P]. (May 2017) - Fernandez, Carlos; Miller, Daniel; Levine, Elliot; Locher, Stephen
Abstract : INTRODUCTION: In 2015, the American Journal of Obstetrics and Gynecology published an opinion supporting ultrasound as the first-line imaging choice in obstetrics and gynecology. Recent advances in 3D gynecologic ultrasound, which includes volumetric calculation and Power Doppler Angiography (PDA) have expanded the practical functionality and diagnostic ability for complex gynecologic conditions. The authors seek to demonstrate this with a case series, comparing the imaging results and the clinical value obtained. METHODS: The described case series includes: 1) Case of missing/broken/embedded IUD complication: located and characterized with 3D gynecologic ultrasound; 2) Case of deeply invasive endometriosis: characterized with 3D gynecologic ultrasound; 3) Improved mapping of uterine fibroids for definitive surgical treatment: characterized by 3D gynecologic ultrasound; 4) Case of endometrial cancerous polyp in a 28 year old, identified with 3D, PDA, volumetric calculation, histogram and Vascularity Index (VI); 5) Case of endometrial carcinoma after negative biopsies: diagnosed via 3D gynecologic ultrasound; 6) Case of an intramural ectopic pregnancy: diagnosed and managed with 3D, PDA, volumetric calculation, histogram and VI. RESULTS: Our case series demonstrates the substantial clinical benefit this modality offers over traditional 2D ultrasound, as well as CT and MRI. Each case shows a unique application of advanced ultrasound technique in gynecologic practice. CONCLUSION: Advances in gynecologic ultrasound are underutilized in current practice. Gynecologists should be aware of the availability and benefits that can result from the use of these advances.